The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3762/bjoc.11.72
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multivalent carbohydrate mimetics with aminopolyol end groups and their evaluation as L-selectin inhibitors

Abstract: SummaryIn this article a series of divalent and trivalent carbohydrate mimetics on the basis of an enantiopure aminopyran and of serinol is described. These aminopolyols are connected by amide bonds to carboxylic acid derived spacer units either by Schotten–Baumann acylation or by coupling employing HATU as reagent. The O-sulfation employing the SO3·DMF complex was optimized. It was crucial to follow this process by 700 MHz 1H NMR spectroscopy to ensure full conversion and to use a refined neutralization and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[23,24] These studies demonstrated that the binding affinity to Lselectin increases with the epitopes' valency from monovalent epitopes like azidopyranes and azidoopexanes to their trivalent presentation. [24,25] It was determined that AuNS can be display 1000-5000 ligands on their surface, what results in even higher binding affinities at sub-nanomolar concentrations. [26] We thus hypothesize that the specific design of the ligand nanoparticle conjugate is a critical parameter which not only defines the efficiency of selectin inhibitors but also strongly regulates immune cell motility.…”
Section: Resultsmentioning
confidence: 99%
“…[23,24] These studies demonstrated that the binding affinity to Lselectin increases with the epitopes' valency from monovalent epitopes like azidopyranes and azidoopexanes to their trivalent presentation. [24,25] It was determined that AuNS can be display 1000-5000 ligands on their surface, what results in even higher binding affinities at sub-nanomolar concentrations. [26] We thus hypothesize that the specific design of the ligand nanoparticle conjugate is a critical parameter which not only defines the efficiency of selectin inhibitors but also strongly regulates immune cell motility.…”
Section: Resultsmentioning
confidence: 99%
“…[26] We recently reported optimizations of the O-sulfation step of multivalent carbohydrate mimetics connected with amide bonds and the commercially available sulfur trioxide-DMF complex was found to be the reagent of choice. [9] It was employed in (deuterated) DMF, thus allowing to follow the reaction progress with high-resolution 1 H-NMR spectroscopy. Here we present the successful application of this method for the O-sulfation of 3-azidopyran 2 and multivalent carbohydrate mimetics bearing 1,2,3-triazole units (Scheme 8).…”
Section: Resultsmentioning
confidence: 99%
“…bonds to compounds of general structure C with rigid or flexible linker units. [9] Similar compounds could be prepared by reductive amination. [10] In this report, we employ enantiopure 3-azido-substituted pyran 2 to synthesize the related divalent products D that are connected via 1,2,3-triazole units.…”
Section: Introductionmentioning
confidence: 99%
“…Amide bond formation to couple 21 and 22 proceeded well with benzotriazol-1-yl-oxytripyrrolidinophosphonium hexafluorophosphate (PyBOP) and N,N -diisopropylethylamine (DIPEA) as 80% spacer-bridged divalent ST14 antigen 23 was produced ( Scheme 3 B). 1-[Bis(dimethylamino)methylene]-1 H -1,2,3-triazolo[4,5- b ]pyridinium 3-oxide hexafluorophosphate 36 (HATU) also successfully catalyzed the coupling but produced some unidentified byproducts. Removal of all of the ester and ether protecting groups of 23 using the same procedure that was used for compound 4 yielded deprotected divalent ST14 2 , containing 2 RU.…”
Section: Resultsmentioning
confidence: 99%